Dėl prūsų kalbos artikelio - Parenti, Alessandro (Baltistica, 1995)
ON THE OLD PRUSSIAN ARTICLE There is evidence of the presence of the article in Old Prussian (evidently due to the influence of German), so that the use of stas as an article in Old Prussian texts is not to be considered a mistake on the part of the translators. In Catechisms I and II, in correspondence with the German definite article, nouns in the nominative and accusative cases are regularly preceded by stas, whereas nouns in the genitive never have stas (for the dative case we have no data). A cross-linguistic comparison shows that it is possible to have a differentiation of this kind in the occurrence of definite markers according to the ease. Since nouns in the genitive regularly take the article in the Enchiridion, the difference between Catechisms I and II and the Enchiridion may reflect partially different dialects.